A representação da surdez no contexto das histórias em quadrinhos: análise do personagem Humberto da Turma da Mônica - PAIXÃO, Priscila Silva da (2025)
This work brings as problematic: How is deafness represented in the context of comics, based on the analysis of the character Humberto of Mônica’s Gang? From this problem we have the following guiding questions: What is Representation? What is the profile of the character Humberto in the context of the Comics of Monica? How is deafness represented in the context of comics, based on the analysis of the character Humberto of Mônica’s Gang? In what way did the changes of representations on deafness occur throughout the comic book publications of Monica's Class? To answer these questions we have as a general objective to analyze how the deafness is represented in the context of the comics, based on an analysis of the character Humberto of Mônica’s Gang. Specifically we intend to approach theoretically the concept of Representation and to describe the profile of the Humberto character in the context of the Comics of the Monica Class; To investigate how deafness is represented in the context of comics, based on the analysis of the character Humberto of Mônica’s Gang; To analyze the changes of representations about the deafness throughout the comics publications of the Class of Monica. The authors who theoretically supported our study were: Pesavento (2005); Skliar (1998, 2003, 2010, 2011), Sperber (2001); Vergueiro (2004), and among others. The methodological procedures of our study refer to a qualitative research characterized as a bibliographic study with characteristic of a documentary analysis, in which we used five comic books to describe how the deafness is represented in the context of the Comics of the Monica And how the character Humberto is labeled and represented in the comic books. This work focuses on special education and emerged as a result of our perceptions about the deafness representations produced in the Comics of Monica, in which they present hearings about the character Humberto (deaf). Through oral culture, discourses are inserted in the comic books, which are often traditional, mark deafness over time as a person who is unable to express himself or express his or her thinking. In the present study, we present representations about the Humberto character, and relate such representations to the changes provoked by the assumptions of Law 10.436 / 2002.